Vitamin C supplementation in laying Japanese quails and its effect on egg performance and quality - Vela Garcia, Carlos Cristobal (2020)
The aim of this study was to evaluate the effect of vitamin C supplementation in mid-laying Japanese quail on productive performance and egg quality. Eighty quails of 23 weeks of age initiating the second third of laying were used. The birds were housed in 20 cages (four birds per cage) and distributed in a completely randomized design with four levels of inclusion of vitamin C in the basal diet: 0, 100, 200 and 300 mg of vitamin C per 100 kg of feed. As productive performance, the feed intake (g/bird/day), laying percentage and feed conversion were determined. Additionally, the weight, height and length of the egg, the height and weight of the yolk and the albumin, and shell thickness were measured as egg quality variables. Vitamin C supplementation at increasing levels in the diet of quails had no effect on productive performance and egg quality, except on shell thickness (p<0.05).